(untitled) (Global Journal of Human-Social Science, 2024)
In today’s world, there is a growing concern about environmental preservation and the impact of human actions on it. The Brazilian Panel on Climate Change highlights the interference of these actions, which reach a global scale and unprecedented magnitude. The intensification of carbon dioxide (CO2) emissions into the atmosphere since the Industrial Revolution has been a significant factor in global climate change and the intensification of the greenhouse effect. Therefore, the objective of this thesis is to investigate the impact of energy consumption and economic growth on carbon dioxide emissions. This thesis is classified as explanatory research and is characterized by a quantitative approach. The final sample consisted of 69 countries, observed for a period of 11 years; the data were collected from the World Bank database. The analysis was carried out using the dynamic panel data structural model with fixed effects, estimated by Maximum Likelihood. The research concludes that: i) for a 1% increase in countries’ income, there was an 0.18% increase in CO2 emissions; ii) a 1% increase in renewable energy consumption had the positive effect of reducing emission levels by 0.12%; iii) however, the increase in non-renewable energy consumption aggravated the carbon dioxide problem by 0.2%; iv) a 1% increase in the total population caused a 0.21% increase in CO2 emissions; v) for a 1% increase in countries’ credit, there was a 0.13% increase in CO2 emissions.